PSYCHOGENETICS: THE DEPTHS OF THE GENETIC ROOTS OF MENTAL DEVELOPMENT (British Journal of Global Ecology and Sustainable Development, 2024)
Psychogenetics is a fascinating field in psychology based on the study of genetic and biological factors that affect human mental development. In this article, we will explore the basic principles of psychogenetics and its importance in understanding how genetic factors influence personality formation, learning abilities, and emotional characteristics.